Dziennik w ścisłym znaczeniu tego wyrazu. Szczęśliwa porażka Bronisława Malinowskiego - Pacukiewicz, Marek (Er(r)go. Teoria - Literatura - Kultura, 2004)
Marek Pacukiewicz A Diary in the Strict Sense of the Term. Bronislaw Malinowski's Fortunate Defeat Inspired by two images of Bronislaw Malinowski made by Witkacy and the idea of repetition which they inevitably evoke, the author points to the essential duality characterising Malinowski' s Diary. The duality in question is the one between the sublime metaphysics of the mind/spirit and the dogging corporeality of the body. This particular opposition is also reflected in Malinowski's language which remains unintentionally transgressive, always on the verge of succumbing to its internal centrifugal force questioning its internal metaphysical element in favour of the discourse of emptiness and melancholy. Thus, following Joseph Conrad, Malinowski's Diary inscribes itself into the context of 19th "crisis of metaphysics" which eventually opens up a path to ontological identity located between repetition and mask and susceptible to the dynamics of ontological mobility.